A review on lightweight methodologies / Zuriani Ahmad Zukarnain, Roslan Jamaludin and Nor Zalina Ismail - Zukarnain, Zuriani Ahmad; Jamaludin, Roslan; Ismail, Nor Zalina (2005)
System Development Life Cycle methodologies are traditional mechanisms to assure that software systems meet established requirements. Traditional methodologies sometimes fall short in the new e-business environment. They are often to "heavy" to keep up with the pace of e-business software development projects. In response to this problem, "light" SDLC methodologies have recently been developed and widely used. This paper begins with a brief overview of traditional SDLC processes. This is followed by an in-depth look at new lightweight methodologies. In this discussion, methods such as Adaptive Software Development (ASD), Agile Software Process (ASP), Crystal, Dynamic System Development Method (DSDM), Extreme Programming (XP), Feature Driven Development (FDD), Rational Unified Process (RUP), SCRUM, and Whitewater Interactive System Development with Object Models (Wisdom) were explored. The paper concludes with a summary of lightweight SDLC methods along with recommendations for their use.